PENINGKATAN KINERJA ADMINISTRATIF: Evaluasi Keberhasilan Aplikasi e-SINAR dalam Penataan Manajemen Persuratan BKKBN Provinsi Sulawesi Tenggara - Arifin Utha; Sartono; Risqoh Nur Ainun (Journal Publicuho, 2023)
This research aims to determine the effectiveness of implementing the e-sinar application in managing correspondence management at the Representative Office of the National Population and Family Planning Agency for Southeast Sulawesi Province using qualitative descriptive methods. Informants were selected purposively. Data collection techniques through in-depth interviews and documentation. The results showed that the application of the E-Sinar Application in managing correspondence at the Representative Office of the National Population and Family Planning Agency (BKKBN) of Southeast Sulawesi Province as a whole was not fully effective as seen from the fact that there are still factors that hinder the effective application of e-sinar to manage correspondence using the system, but with the application of e-sinar to manage correspondence it becomes easier for employees in terms of performance in the form of the amount of work produced by employees and the time it takes to manage correspondence using e-sinar is much faster, accurate and relevant. Then with the application of e-sinar employees can more easily find archived letters when needed again, this makes employee performance and organizational performance more measurable. The inhibiting factors in running the e-sinar application are work culture factors that are still accustomed to the conventional mail management process and internet facilities and networks.